2021
DOI: 10.1021/acs.organomet.1c00525
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Modular Synthesis of [Cp*Rh] Monohydrides Supported by Chelating Diphosphine Ligands

Abstract: Supporting Information PlaceholderABSTRACT: [Cp*Rh] hydride complexes are invoked as intermediates in certain catalytic cycles, but few of these species have been successfully prepared and isolated, contributing to a relative shortage of information on the properties of such species. Here, the synthesis, isolation, and characterization of two new [Cp*Rh] hydrides are reported; the hydrides are supported by the chelating diphosphine ligands bis(diphenylphosphino)methane (dppm) and 4,5-bis(diphenylphosphino)-9,9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 65 publications
(74 reference statements)
2
18
0
Order By: Relevance
“…[36] To confirm our assignment of these resonances, we carried out multifrequency NMR experiments at 400, 500, 600, and 800 MHz that confirm the involvement of second-order effects which are visible in the spectra as "roofing". [37,38] Digital simulations of the field-dependent spectra reproduced the experimental data, confirming our assignment (Figure S26).…”
Section: Chemistry-a European Journalsupporting
confidence: 83%
“…[36] To confirm our assignment of these resonances, we carried out multifrequency NMR experiments at 400, 500, 600, and 800 MHz that confirm the involvement of second-order effects which are visible in the spectra as "roofing". [37,38] Digital simulations of the field-dependent spectra reproduced the experimental data, confirming our assignment (Figure S26).…”
Section: Chemistry-a European Journalsupporting
confidence: 83%
“…Eager to further interrogate this species, we repeated this protonation experiment with IR monitoring, providing unequivocal evidence from vibrational data for the formation of [Cp*Rh(H)(bpy)] + (4) based on a characteristic Rh-H stretch at 1920 cm -1 (Figure 5). Notably, this value is similar to other Rh-H stretches (1986-1936 cm -1 ) previously reported by our group for analogous [Cp*Rh] monohydride complexes ligated by bisphosphine ligands, albeit slightly lower in energy, and is in good agreement with our DFT-calculated spectrum (1920 vs 1902 cm -1 , respectively, see SI, Figure S32) (24,26). The UV-vis spectrum of 4 displays a prominent absorption at 400 nm and weaker features that tail into the visible region.…”
Section: Initial Proton Transfer and Tautomerizationsupporting
confidence: 92%
“…To this point, 3 exhibits vivid pigmentation, attributable to delocalization of electron density by π-backbonding into the bpy π-system (45). The properties of bpy thus strongly influence the catalytic reactivity paradigm observed, reactivity that is not echoed in systems supported by bidentate bisphosphine ligands (24,26) or even the closely related 9,9′-dimethyl-4,5diazafluorene ligand (43), as well as impart spectral uniqueness to the [Cp*Rh] system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, reduction of NAD + can be conducted by chemical, photochemical, enzymatic, and electrochemical means. To be specific, vast development in the field of organometallic chemistry cultivated numerous chemical regeneration catalysts including organometallic complexes of ruthenium, iridium, and rhodium. , Rhodium complexes, in particular, feature improved 1,4-regioselectivity, high stability, and very good activity, making rhodium-incorporated organometallic catalysts the best prospects. The main drawbacks of hitherto presented rhodium complexes are, however, their low TOFs and a consequent increase in the concentration of added catalyst. , In order to overcome the shortcomings, improved activity of the catalyst is necessary . Extensive research has been done to address the issue, and this led to isolation of the first catalytic intermediate of [Cp*Rh­(bpy)­Cl] + with a Cp*–H fragment, (Cp*H)­Rh­(bpy)­Cl. , Furthermore, recent studies on rhodium complexes with phosphine-containing ligands reported the isolation of stable rhodium hydride complexes. However, these findings opened a new debate regarding the structure of the intermediate through which the hydride is transferred to NAD + , either directly via a Rh–H intermediate or by its equilibrium tautomer with a η 4 -Cp*H moiety. Previous studies show that, to achieve a fast intermediate generation, increased electron density on the metal center with more electron-donating ligand systems is essential. , Yet, the relationship between the reaction rate and the form of the intermediate has not been intensely scrutinized.…”
Section: Introductionmentioning
confidence: 99%